2012
DOI: 10.1158/1078-0432.ccr-12-0701
|View full text |Cite
|
Sign up to set email alerts
|

Let-7 Expression Is a Significant Determinant of Response to Chemotherapy through the Regulation of IL-6/STAT3 Pathway in Esophageal Squamous Cell Carcinoma

Abstract: Purpose: Cisplatin-based chemotherapy is widely used for esophageal cancer, sometimes in combination with surgery/radiotherapy, but poor response to chemotherapy is not uncommon. The aim of this study was to examine whether miRNA expression is useful to predict the response to chemotherapy in patients with esophageal cancer.Experimental Design: Using pretreatment biopsy samples from 98 patients with esophageal cancer who received preoperative chemotherapy, we measured the expression level of several miRNAs who… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 32 publications
4
116
0
Order By: Relevance
“…Downregulation of let-7 was also associated with chemoresistance in breast cancer cells (39). In addition, Sugimura et al (38) reported that low expression of let-7b and let-7c was significantly associated with a poor response to chemotherapy in esophageal squamous cell carcinoma, and that transfection of let-7c restored sensitivity to cisplatin and increased the rate of apoptosis following exposure to cisplatin in vitro assays. Additionally, Tsang and Kwok (34) reported that induced expression of let-7a increased the resistance of human squamous carcinoma A431 cells to chemotherapeutic drugs, including interferon-γ, doxorubicin and paclitaxel.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Downregulation of let-7 was also associated with chemoresistance in breast cancer cells (39). In addition, Sugimura et al (38) reported that low expression of let-7b and let-7c was significantly associated with a poor response to chemotherapy in esophageal squamous cell carcinoma, and that transfection of let-7c restored sensitivity to cisplatin and increased the rate of apoptosis following exposure to cisplatin in vitro assays. Additionally, Tsang and Kwok (34) reported that induced expression of let-7a increased the resistance of human squamous carcinoma A431 cells to chemotherapeutic drugs, including interferon-γ, doxorubicin and paclitaxel.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, emerging evidence has demonstrated that members of the let-7 family of miRNAs are downregulated in a number of types of human cancer, and that low let-7 expression has been correlated with resistance to chemotherapeutics (37,38). Downregulation of let-7 was also associated with chemoresistance in breast cancer cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs, including miR-21, miR-31, miR-577, etc, act as oncogenes, [19][20][21] while others such as Let-7, miR-98, miR-100, miR-138, miR-143, miR-150, etc, function as tumor suppressors. [22][23][24][25][26][27] However, the role of miR-186 in ESCC progression remains uninvestigated.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, an inverse correlation of miR-138 levels and NF-κB expression in ESCC patient samples provides further support for this regulation. Let-7, a tumor suppressor miRNA downregulated in multiple forms of cancer, including ESCC, 63 downregulates Ras and IL-6, well-known oncogenes which are upstream activators of the NF-κB pathway. 64 Other miRNAs may have pro-oncogenic effects through stimulation of NF-κB signaling.…”
Section: Non-coding Rnas Regulating/ Regulated By Nf-κb Pathway In Esccmentioning
confidence: 99%